2016
DOI: 10.15406/mojcr.2016.05.00133
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Ovarian Masses Measuring ≥5cm in Pregnancy - a Series of Six Cases

Abstract: Ovarian masses ≥5cm in diameter have been found in only 0.04-0.05% of pregnant women. Most of the adnexal masses encountered during pregnancy are simple cysts <5cm in diameter and about 70% would resolve by the early second trimester. The persistent cysts with gradual increase in size required surgical management. Adnexal masses requiring surgical intervention in pregnancy have been reported for around 1% to 2.3% of all gestations. In the series we reviewed 6 cases at different trimesters of pregnancy with ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…9 Whitecar et al in their cohort of 130 cases reported a mean age of 26.1 years. 5 All the six cases in our study were unilateral similar to that seen by Fatema et al and Ulker et al 10,11 The most common and serious complication of benign ovarian cysts during pregnancy remains torsion of the cyst which is more prevalent in larger cysts. Yen et al in their series of 174 women reported a higher risk of torsion in cysts measuring 6-8 cm in size.…”
Section: Discussionsupporting
confidence: 86%
“…9 Whitecar et al in their cohort of 130 cases reported a mean age of 26.1 years. 5 All the six cases in our study were unilateral similar to that seen by Fatema et al and Ulker et al 10,11 The most common and serious complication of benign ovarian cysts during pregnancy remains torsion of the cyst which is more prevalent in larger cysts. Yen et al in their series of 174 women reported a higher risk of torsion in cysts measuring 6-8 cm in size.…”
Section: Discussionsupporting
confidence: 86%
“…Acute abdominal pain is an indication for emergency measures for pregnant women. 3 The ideal time for an operative pregnancy with an ovarian cyst> 5 cm is performed at the age of the second trimester of pregnancy, but if there are twisted cysts then an emergency surgery is performed. 4 The principle of operation must be reemphasized to reduce the rate of postoperative adhesion and subfertility.…”
Section: Introductionmentioning
confidence: 99%